Five years of advances in electrochemical analysis of protein biomarkers in lung cancer: a systematic review - Regiart, Matías; Fernández-Baldo, Martín A.; Navarrete, Bernardino Alcázar; Morales García, Concepción; Gómez, Beatriz; Tortella, Gonzalo R.; Valero, Teresa; Ortega, Francisco Gabriel (Frontiers in Chemistry, 2024)
Lung cancer is the leading cause of cancer death in both men and women. It represents a public health problem that must be addressed through the early detection of specific biomarkers and effective treatment. To address this critical issue, it is imperative to implement effective methodologies for specific biomarker detection of lung cancer in real clinical samples. Electrochemical methods, including microfluidic devices and biosensors, can obtain robust results that reduce time, cost, and assay complexity. This comprehensive review will explore specific studies, methodologies, and detection limits and contribute to the depth of the discussion, making it a valuable resource for researchers and clinicians interested in lung cancer diagnosis.